2011
DOI: 10.1080/00221325.2010.526975
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Efficacious Self-Presentation Scale

Abstract: A new self-report measure of adolescent's self-presentation is described. The self-report scale was administered to 760 16-19-year-old subjects. Results of a factor analysis supported 6 identifiable factors reflecting different concepts, theoretically discussed, related to self-presentation: ability to regulate self-image, social sensitivity, body self-confidence, social self-confidence, social openness, and social desirability. The scale showed good convergent validity and internal consistency. Assertive tact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Other studies have reported that dysfunctional families and inadequate parenting styles, for example lower levels of parental emotional warmth, parental overprotection, and parental rejection, were associated with the onset and persistence of SAD in children (Knappe et al., , ; van Oort et al., ). Given that the FS subscale of the OSIQ describes family relationships in terms of lower levels of intergenerational conflicts, good feelings and positive relationships with parents, close communication, and a supportive climate, a potential explanation for our finding is that high scores in the family relationships subscale reflected an overprotective family environment which restricted the development of autonomy and social competence (Laghi et al., ; Lieb et al., ). In the sociocultural context of Southern Italy, the line between overprotective and harmonious, low‐conflict family relationships is often a fine one, especially for young women.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Other studies have reported that dysfunctional families and inadequate parenting styles, for example lower levels of parental emotional warmth, parental overprotection, and parental rejection, were associated with the onset and persistence of SAD in children (Knappe et al., , ; van Oort et al., ). Given that the FS subscale of the OSIQ describes family relationships in terms of lower levels of intergenerational conflicts, good feelings and positive relationships with parents, close communication, and a supportive climate, a potential explanation for our finding is that high scores in the family relationships subscale reflected an overprotective family environment which restricted the development of autonomy and social competence (Laghi et al., ; Lieb et al., ). In the sociocultural context of Southern Italy, the line between overprotective and harmonious, low‐conflict family relationships is often a fine one, especially for young women.…”
Section: Discussionmentioning
confidence: 85%
“…An earlier study (Suriadi, Lorenz, Wickrama, & Conger, ) noted that ability to control and manage the environment protects adolescents' well‐being in adversity. With a similarly aged sample, Laghi, Pallini, D'Alessio, and Baiocco () found that ability to regulate self‐image predicted assertive tactics during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…School approaches aimed at reducing feelings of revenge and anger, and improving emotional regulation and prosocial behavior may be helpful to reduce bullying episodes in both traditional and cyber forms [15,49,50]. Anger-management programs for children and adolescents may be quite effective [22], constitute a time-efficient mode of brief intervention by school psychologists.…”
Section: Resultsmentioning
confidence: 97%
“…Individual self-presentation strategies were assessed by a selection of items from the habitual self-presentation scales by Merzbacher (2007), who built on the self-presentation tactics scale by Lee et al (1999). We focused on those facets of self-presentation, which we assumed as particularly relevant in the context of selfies, i.e., self-promotion and self-disclosure.…”
Section: Methodsmentioning
confidence: 99%